2021
DOI: 10.1108/intr-10-2020-0589
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors and mechanism of doctor consultation volume on online medical consultation platforms based on physician review analysis

Abstract: PurposeThis paper aims to reveal the factors patients consider when choosing a doctor for consultation on an online medical consultation (OMC) platform and how these factors influence doctors' consultation volumes.Design/methodology/approachIn Study 1, influencing factors reflected as service features were identified by applying a feature extraction method to physician reviews, and the importance of each feature was determined based on word frequencies and the PageRank algorithm. Sentiment analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…However, with the rising consultation volume, the SHAP value declines continuously until reaching the minimum value. Thus, we reckon consultation volume has a strong negative effect on service satisfaction due to the limited distribution of health and medical resources (Wan et al 2021 ). And the number of free and fee-based consultations affects service satisfaction differently.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the rising consultation volume, the SHAP value declines continuously until reaching the minimum value. Thus, we reckon consultation volume has a strong negative effect on service satisfaction due to the limited distribution of health and medical resources (Wan et al 2021 ). And the number of free and fee-based consultations affects service satisfaction differently.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some empirical studies have provided supports for the relationships between online health platform information, online trust and the willingness to do online health consultation. On one hand, previous studies have directly shown the significant relationship between the online information and patients' trust in physicians (27). On the other hand, studies have revealed that online trust was a driving factor influencing online purchase (28), which provided supports for the relationship between online trust and the willingness to do online health consultation.…”
Section: The Mediating Role Of Online Trustmentioning
confidence: 89%
“…Sentiment analysis According to the method described in Section 4.3 , it first needs to determine the topics in the review. Referring to previous relevant literature [ 29 ] and validated in training dataset annotation process, it selects and categorizes the evaluation information into four topics. Each topic will be briefly introduced in the following.…”
Section: Case Study: Doctor Selection In Dxycommentioning
confidence: 99%